Effect of sleeping position on arousals from sleep in preterm infants. Issue 3 (25th May 2016) - Modesto, Ingrid Felix; Avelar, Ariane Ferreira Machado; Pedreira, Mavilde da Luz Gonçalves; Pradella‐Hallinan, Marcia; Avena, Marta José; Pinheiro, Eliana Moreira
Abstract: Purpose: To evaluate the frequency of preterm infant positions during sleep, and to investigate the association among positions, arousals, sleep patterns, and time of day. Design and Methods: This observational study was conducted in a neonatal unit with 10 preterm infants. Polysomnographic and video recordings during 24 hr identified sleep positions, arousals, sleep patterns, and time of day. Results: Preterm infants were placed most frequently in the supine position (58.4%), followed by right side (24.9%), left side (15.5%), and prone (1.2%). The longest amount of time spent sleeping, and the most frequent number of arousals, occurred in the supine position, followed by prone, left‐side, and right‐side positions. After controlling for length of time spent in each position, the number of arousals per hour was the greatest in the supine position (13.562 ± 0.732) and least in the prone position (11.56 ± 4.754; p  < .001). There were no significant differences in arousals according to position and sleep pattern (indeterminate, quiet, active sleep) or position and time of day (morning, afternoon, twilight, night). Practice Implications: Nurses should evaluate the frequency of preterm infant arousals in each position, and use more often those positions that lead to a lower frequency of arousals and better sleep quality.